Optimized small‐molecule pull‐downs define MLBP1 as an acyl‐lipid‐binding protein. (19th March 2019) - Sterlin, Yelena; Pri‐Tal, Oded; Zimran, Gil; Park, Sang‐Youl; Ben‐Ari, Julius; Kourelis, Jiorgos; Verstraeten, Inge; Gal, Maayan; Cutler, Sean R.; Mosquna, Assaf
Summary: Abscisic acid (ABA) receptors belong to the START domain superfamily, which encompasses ligand‐binding proteins present in all kingdoms of life. START domain proteins contain a central binding pocket that, depending on the protein, can couple ligand binding to catalytic, transport or signaling functions. In Arabidopsis, the best characterized START domain proteins are the 14 PYR/PYL/RCAR ABA receptors, while the other members of the superfamily do not have assigned ligands. To address this, we used affinity purification of biotinylated proteins expressed transiently in Nicotiana benthamiana coupled to untargeted LC‐MS to identify candidate binding ligands. We optimized this method using ABA–PYL interactions and show that ABA co‐purifies with wild‐type PYL5 but not a binding site mutant. The K d of PYL5 for ABA is 1.1 μm, which suggests that the method has sufficient sensitivity for many ligand–protein interactions. Using this method, we surveyed a set of 37 START domain‐related proteins, which resulted in the identification of ligands that co‐purified with MLBP1 (At4G01883) or MLP165 (At1G35260). Metabolite identification and the use of authentic standards revealed that MLBP1 binds to monolinolenin, which we confirmed using recombinant MLBP1. Monolinolenin also co‐purified with MLBP1 purified from transgenic Arabidopsis, demonstrating that the interaction occurs in a native context. Thus, deployment of this relatively simple method allowed us to define a protein–metabolite interaction and better understand protein–ligand interactions in plants. Significance Statement: Proteins are ubiquitous in all cellular organisms, but it is their interactions with metabolites that are often critical to their functions. We optimized an affinity‐purification and LC/MS method for discovery of protein–small molecule interactions, which may prove valuable in bridging gaps in our understanding of protein functions.